Secondary metabolite profiles and mating population of Fusarium species in section Liseola associated with bakanae disease of rice - Mohd Zainuddin, Nur Ain Izzati; Abd Razak, Azmi; Salleh, Baharuddin (Malaysian Society for Microbiology, 2008)
A total of 25 strains of Fusarium species that belong to F. fujikuroi (a pathogen of bakanae disease), F. proliferatum, F.sacchari, F. subglutinans and F. verticillioides were isolated from rice plants showing typical bakanae symptoms in Malaysia and Indonesia and screened for their secondary metabolites. The objectives of the studies were to determine the physiological variability based on production of moniliformin (MON), fumonisin (FB1), gibberellic acid (GA3) and fusaric acid(FA) as well as to ascertain the mating populations (MPs) within the Gibberella fujikuroi species complex based on their ability to produce perithecia and viable ascospores. Production of GA3 could be used to separate F. fujikuroi that belongs to MP-C from other species. In crosses with seven standard testers of MPs, 76% of strains could be assigned to at least one of the G. fujikuroi species complex namely MP-A (G.moniliformis), MP-B (G. sacchari), MP-C (G. fujikuroi) and MP-D (G.intermedia). Single strain (M3237P) that was assigned as MP-C, and has also been identified morphologically as F. fujikuroi was also crossed-fertile with MP-D tester. The secondary metabolites profiles and the presence of MP-A, MP-B, MP-C and MP-D strains on samples of bakanae-infected rice plants are new records in Malaysia.